Analisis Performa Owncloud Dan Pydio Pada Aplikasi Layanan Cloud Storage - Vinsensius Elman Mendrofa; Tommy; Risko Liza (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The comparison analysis of owncloud and pydio performance refers to testing the performance of open sourcecloud storage service applications by identifying the use of resource consumption and technical use of the networkbetween the two cloud services as a benchmark for users and can be used as a basis for selecting cloud storageapplications that meet the criteria for save data. Performance comparison testing is done by uploading a file to acloud service, then resource usage will be monitored using netdata, and for technical network usage it will bemonitored using wireshark. For the results of testing the performance of owncloud and pydio services, in terms ofresource usage and consumption, owncloud is lighter than pydio. On the technical use of the network both havethe same level of criteria. However, for the user interface, pydio has an attractive appearance and is easy to use.